Enhancing Waqf Forest Sustainability Through Agroforestry: Case Study from Bogor Waqf Forest, Bogor, Indonesia - Miftahul Jannah; Khalifah Muhamad Ali; Brigita Laura Fatria; Azila Ahmad Sarkawi; Jamilah Othman (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
The high rate of forest conversion in Indonesia required further actions to overcome. One of the solutions is through waqf (endowment) forest, a forest developed on waqf land. According to Islamic law, a waqf forest cannot be sold, granted, inherited, or changed unreasonably. Previous researches generally focused more on the potential and prospect of cash waqf or land waqf for forest protection. On the other hand, a study to enhancing waqf forest sustainability still needs to be developed, especially in Indonesia. This paper aims to observe the practice of agroforestry to enhance the sustainability of waqf forest, with the case study location in the Bogor Waqf Forest, Cibunian Village, Pamijahan District, Bogor Regency, Indonesia. The present study was conducted from March 2019 until June 2021, using a literature study, observation, and in-depth interview method then analyzed descriptively. Agroforestry practices are chosen in the case study location, such as agrosilvicultural, agrosilvopastoral, and agrosilvofishery. Based on the Sustainable Forest Management (SFM) goals, agroforestry practices in waqf forests are estimated to extend forest resources, increase biodiversity, forest health, forest production, and protection functions, and contribute to social and economic development benefits. Tingginya alihfungsi lahan hutan di Indonesia memerlukan usaha lebih untuk mengatasinya. Salah satu solusinya adalah melalui program hutan wakaf, yaitu hutan yang dibangun di atas tanah wakaf. Berdasarkan hukum Islam, hutan wakaf tidak boleh dijual, diberikan, diwariskan, dan diubah fungsi lahannya tanpa alasan yang dibenarkan. Penelitian-penelitian sebelumnya lebih berfokus pada potensi dan prospek dari wakaf uang atau wakaf tanah untuk melindungi hutan. Studi mengenai upaya pelestarian hutan wakaf masih perlu untuk dilakukan, terutama di Indonesia. Studi ini dilakukan pada bulan Maret tahun 2019 hingga Juni tahun 2021, berlokasi di Hutan Wakaf Bogor, Desa Cibunian, Pamijahan, Kabupaten Bogor, Indonesia, menggunakan metode studi literatur, observasi lapang, dan wawancara pakar yang kemudian dianalisis secara deskriptif. Beberapa praktik agroforestri dipilih untuk diaplikasikan pada lokasi studi, seperti agrosilvikultura, agrosilvopastoral, dan agrosilvofishery. Berdasarkan tujuan pengelolaan hutan lestari (SFM), praktik agroforestri pada hutan wakaf diestimasikan tidak hanya meningkatkan sumber daya hutan, biodiversitas, kesehatan, produksi, dan perlindungan hutan, tetapi juga memiliki manfaat sosial dan ekonomi.